Investigation of Lesions In Goat Brain Collected From Abattoirs in Rajshahi Metropolitan Area (Journal of Bio-Science, 2021)
Brain lesions are important cause of morbidity and reduced productivity in goats worldwide. Works on brain lesion in goats are extremely rare in Bangladesh and remain to be investigated. We investigated lesions in goat brains collected from abattoirs in Rajshahi Metropolitan area by gross and microscopic examination. Randomly selected 57 goat brains were investigated of which 24.56% brains showed gross and histopathologic lesions. Prevalence of brain lesions were higher in Jamnapari goats (29.41%) compared to in Black Bengal goats (22.50%) and female goats (26.47%) were more affected than male goats (21.74%). Age-wise prevalence were 31.25%, 21.43%, 12.50%, and 40.00% in the age of up to 2 years, 2-3 years, 3-4 years, and above 4 years old goats, respectively. Goats were more affected in the rainy (35.29%) season in contrast to in the winter (23.53%) and in the summer (10.52%) seasons. The brains collected from goats with Gid disease showed uni or multilocular cysts containing clear fluid and multiple scolices, the rest of the brains were apparently healthy by macroscopic examination. Histopathologically, pyogranuloma, perivascular cuffing, gliosis, neuronal degeneration, hemorrhages, congestion and thrombus were evident.J. Bio-Sci. 29(1): 49-58, 2021 (June)